TRENDS IN HIGHER VOCATIONAL EDUCATION: PROFESSIONALIZATION OR DEPROFESSIONALIZATION? - Yu. R. Vishnevsky; D. Yu. Narkhov; Ya. V. Didkovskaya (Russian State Vocational Pedagogical University, 2018)
Introduction. Student population is the most important social resource of development of post-industrial information society. Therefore, those students will take places of leading experts and will define the level of social and economic wellbeing of the country and its competitiveness in the world in the near future. In this regard, it is important to find out the potential of the student's environment in order to convert it without any loss into social and cultural capital of the state. First of all, this potential is made up by education, qualification and profession and students' valuable relation to their occupation. Thereby, such valuable relation depends on a degree of a future specialist' personal maturity, a degree of his/her responsibility for the activity, and readiness for professional selfimprovement.The aims of the present publication are: to analyse the processes of professional self-determination among students; to reveal the tendencies of students' professional self-determination.Methodology and research methods. The methodological basis of the research involves modern scientific theories formulated within branches of Sociology - Sociology of Education and Sociology of Youth. Representative quota-cluster selective questionnaire survey was used as the main method; that was carried out in seven steps in 1995-2016. The total amount of selection involved 9133 students studying in higher education institutions of Sverdlovsk region - one of the largest administrative territories of Russia.Results and scientific novelty. The results of a unique long-term monitoring are generalized and interpreted. In the course of the monitoring, the dynamics of professional self-determination of student youth was traced by means of such key indicators as follows: motives of the choice of the sphere of employment and educational institution; personal importance of future profession for students; professional plans of students after graduating from a higher education institution. The obtained data refer to a complex of problems and contradictions of functioning of institutes of education and a profession during the period of societal transformations. The main conclusion drawn by the authors consists in the fact of growing tendency towards the deprofessionalization of students.Practical significance. The materials of the research could be useful to design and update vocational guidance of young people.